The role of oxidative stress in gestational diabetes - Kamila Stopińska; Adrianna Marzec (Annales Academiae Medicae Silesiensis, 2023)
Gestational diabetes mellitus (GDM) is one of the most common diseases that leads to complications during pregnancy. It has been noticed that GDM is accompanied by an increase in oxidative stress. The aim of this study is to summarize the state of knowledge on the influence of oxidative stress on the occurrence and course of gestational diabetes as well as its long-term effects. This review also aims to examine the potential clinical implications of GDM. Databases such as Pubmed, Scopus, and Google Scholar were searched. Articles were searched for using the phrases “gestational diabetes mellitus” and “oxidative stress”. A significantly higher level of oxidative stress was found in women with GDM, both in the blood and in the placenta. Oxidative stress may be closely related to the pathogenesis of GDM. Due to the important role of oxidative stress in the pathophysiology of GDM, many studies have focused on finding substances that can reduce the concentration of prooxidants and increase the proportion of antioxidants, thereby improving the oxidative potential. Oxidative stress plays a key role in the pathogenesis and pathophysiology of GDM. As it is a disease that can lead to a number of complications for both the mother and the fetus, its early detection and effective treatment require special attention. Further detailed research is required to evaluate the possibility of using the parameters of oxidative stress as biomarkers for the early detection of GDM.